Sustaining Growth in Korea by Reforming the Labour Market and Improving the Education System - Jones, Randall S.. (OECD Economics Department Working Papers, 2009)
A well-functioning labour market is essential to sustain rapid economic growth in the face of population ageing. Priorities are to reverse the rising share of non-regular workers, which has negative implications for both growth and equity, and encourage greater employment of women and youth, who are under-represented in the labour force. Attracting more women to employment requires increasing the availability of childcare, strengthening maternity leave and creating more family-friendly workplaces. Youth employment rates should be boosted by upgrading tertiary education through stronger competition and closer links to enterprises to reduce mismatches. Educational reform should be extended to elementary and secondary schools to enhance efficiency and decrease the burden of private tutoring. The age of retirement of employees should be raised by eliminating mandatory retirement and phasing out the retirement allowance. Active labour market policies should focus on policies to expand human capital rather than wage subsidies